Meerkats - Marsh, Laura F.; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2013)
Describes the habitat, food habits, and social behaviors of meerkats, and explains how they protect themselves from predators.
What are they? -- All about meerkats -- Terrific tunnels -- On the menu -- Big family -- A job to do -- 7 cool facts about meerkats -- Pups -- Staying safe -- What in the world?
OSLIS\Gale Nat Geo eBooks(2/2/23).
Description based on print version record.
Keywords: Meerkat; Meerkat -- Juvenile literature; Electronic books- OSLIS; Electronic books